1997
DOI: 10.1200/jco.1997.15.4.1587
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictive factors, and outcome of lymphoma transformation in follicular lymphoma patients.

Abstract: Transformation is an early event in the course of the disease and is mainly observed in patients with known adverse prognostic factors or those who do not achieve CR after initial treatment. These findings may be useful to select follicular lymphoma patients for intensive therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
203
2
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(211 citation statements)
references
References 23 publications
2
203
2
4
Order By: Relevance
“…Lastly, it has been reported that 25-35% of patients with follicular lymphoma may undergo histologic transformation to diffuse large B-cell lymphoma and transformation is usually associated with a rapidly progressive clinical course, refractoriness to therapy and death. 1,25 In our series, a much higher percentage of patients (43%) developed diffuse large B-cell lymphoma, whereas only 17% patients from the CD5− follicular lymphoma group developed diffuse large B-cell lymphoma (P o 0.001). Finally, when compared with a group of patients with CD5− follicular lymphoma matched for age, gender, and stage, we found that patients with CD5+ follicular lymphoma had a significantly shorter median progression-free survival.…”
Section: Discussionmentioning
confidence: 53%
“…Lastly, it has been reported that 25-35% of patients with follicular lymphoma may undergo histologic transformation to diffuse large B-cell lymphoma and transformation is usually associated with a rapidly progressive clinical course, refractoriness to therapy and death. 1,25 In our series, a much higher percentage of patients (43%) developed diffuse large B-cell lymphoma, whereas only 17% patients from the CD5− follicular lymphoma group developed diffuse large B-cell lymphoma (P o 0.001). Finally, when compared with a group of patients with CD5− follicular lymphoma matched for age, gender, and stage, we found that patients with CD5+ follicular lymphoma had a significantly shorter median progression-free survival.…”
Section: Discussionmentioning
confidence: 53%
“…[4][5][6][7][8] It is difficult to determine the true incidence as it depends not only on the definition of HT, but also on the frequency and sites of biopsy, duration of follow-up, and the population considered at risk. Optimally, a change in the clinical nature of disease leads to a repeat lymph node biopsy that reveals a progression from follicular to diffuse histology of a higher grade.…”
Section: Incidencementioning
confidence: 99%
“…1 The course of follicular lymphoma is quite variable, with some patients followed expectantly for many years without needing therapy and others having a much more aggressive course with rapid progression, early relapses and eventual transformation to aggressive histology. [2][3][4] Follicular lymphoma remains incurable with conventional treatment modalities and thus the main indication for treatment is the alleviation of disease-related symptoms. Although most patients achieve CR or PR following initial chemotherapy (CT), relapse is inevitable.…”
Section: Introductionmentioning
confidence: 99%